1993
DOI: 10.1523/jneurosci.13-07-02898.1993
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyridine-sensitive calcium current mediates neurotransmitter release from bipolar cells of the goldfish retina

Abstract: The release of neurotransmitter is evoked by activation of the Ca current (ICa) at presynaptic terminals. Though multiple types of ICa have been reported in various cells, little is known about the properties of presynaptic ICa in the vertebrate CNS. The aim of this article is to identify the type of ICa involved in the release of neurotransmitter from retinal bipolar cells. Bipolar cells with a large axon terminal were isolated enzymatically from the goldfish retina, and studied by the following techniques: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
122
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 61 publications
11
122
0
Order By: Relevance
“…Schmitz and Witkovsky (1997) reported that glutamate efflux from Xenopus photoreceptors is blocked by dihydropyridines but is not affected by blockers of N-or P-type calcium channels. The data for rods are similar to those for another nonspiking retinal cell, a depolarizing bipolar cell of the goldfish retina, for which it has been shown that exocytosis and glutamate release is gated by a dihydropyridine-sensitive L -type C a current (Heidelberger and Matthews, 1992;Tachibana et al, 1993).…”
Section: The Dependence Of Glutamate Release On Calciumsupporting
confidence: 73%
See 1 more Smart Citation
“…Schmitz and Witkovsky (1997) reported that glutamate efflux from Xenopus photoreceptors is blocked by dihydropyridines but is not affected by blockers of N-or P-type calcium channels. The data for rods are similar to those for another nonspiking retinal cell, a depolarizing bipolar cell of the goldfish retina, for which it has been shown that exocytosis and glutamate release is gated by a dihydropyridine-sensitive L -type C a current (Heidelberger and Matthews, 1992;Tachibana et al, 1993).…”
Section: The Dependence Of Glutamate Release On Calciumsupporting
confidence: 73%
“…In contrast, at a tonic retinal synapse for which a depolarizing bipolar cell is the presynaptic element, transmitter release is controlled by a dihydropyridinesensitive L -type calcium current (Heidelberger and Matthews, 1992;Tachibana et al, 1993). Rods and cones also possess an L-type C a current (Bader et al, 1982;Corey et al, 1984;Barnes and Hille, 1989;Lasater and Witkovsky, 1991;Wilkinson and Barnes, 1996), and there is evidence that it underlies exocytosis (Rieke and Schwartz, 1996) and glutamate release (Schmitz and Witkovsky, 1997).…”
mentioning
confidence: 99%
“…In Mbs, I Ca is mediated by L-type Ca 2ϩ channels (Tachibana 1999) expressed at the axon terminal with properties reminiscent of Ca V 1.3 (Burrone and Lagnado 1997;Heidelberger and Matthews 1992;Mennerick and Matthews 1998;Tachibana et al 1993;Zenisek and Matthews 1998). The nonlinearity reflected by the Hill coefficient in coding light intensity with Ca 2ϩ influx was greater during spiking than graded Mb responses.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative relationship between the increase in intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) and the number of released synaptic vesicles in Mb terminals has been studied with a variety of techniques from a variety of angles Grabner and Zenisek 2013;Heidelberger et al 1994;Midorikawa et al 2007;Tachibana et al 1993;von Gersdorff et al 1998;Zenisek and Matthews 2000). Here we revisited this relationship by triggering the Ca 2ϩ influx and subsequent exocytosis with depolarizing commands that mimic light-evoked spiking (Mb1) and graded (Mb9, Mb10) V m in response to 500-ms light stimuli (Fig.…”
Section: At the Level Of Transmitter Release Spiking Bipolar Cell Rementioning
confidence: 99%
“…We found that almost all of the depolarization-induced Ca 2ϩ influx in Merkel cells is through two types of channels. These are L-type channels, which trigger neurotransmission in hair cells and retinal bipolar cells (50,51), and P͞Q-type channels, which are found at central synapses (52). Although we found that Merkel cells expressed transcripts encoding Ca V 2.2͞ ␣ 1B , these channels did not significantly contribute to Ca 2ϩ entry.…”
Section: Discussionmentioning
confidence: 99%